Bibliography of the Journal Metalurgija 1962–2026 - Ilija Mamuzić (Metalurgija)
Bibliography of the journal Metalurgija from the first issue published in 1962 until the last issue published in 2025, ga. until the 2026. Content: – 1962 - 2026 the publishing of the Metalurgija Journal - pp. 255 – – Abstract - pp. 255 – – Introduction - pp. 255 – – Foundation and History of the Journal - pp. 258 – – Past Achievements - pp. 261 – – Organization of Journal Activities - pp. 262 – – Metalurgija and Croatian Universities - pp. 265 – – Instead of conclusion - pp. 269 – Acknowledgement to Reviewers, Metalurgija 64 (2025) 1-4, 1-528 - pp. 272 – List of Boards and Co-workers 1962 – 2026 – pp. 273 – List of Published papers 1962 – 2026 – pp. 279 – The fourth certificate to Croatian metallurgical society (CMS) for successfully business (2020, 2021, 2022, 2023 y) – pp. 456 – List of Authors and Co-Authors 1962 – 2026 – pp. 457 – Selected Materials of the Author – pp. 502 – – Publishing Commission, Ministry of Science, Education and sport for Editor-in Chief Ilija Mamuzić 2006 – pp. 502 – – Ministry of Science, Education and sport (MSES), Ministry Dragan Primorac „Financial support of the MSES to Scientific Journal in the field of Technical Science with the example of the Metalurgija Journal“, 2008. – pp. 503 – – Ministry of Science and Education (MSE), Ministry Blaženka Divjak „Openess of science in Croatia by the committee for scientific and publishing activities of MSE“ – pp. 509 – – On the occasion of fifty year (1962 – 2012) publishing of Journal Metalurgija several quotes – pp. 516 – Photo gallery – pp. 517